1990
DOI: 10.1007/bf01977631
|View full text |Cite
|
Sign up to set email alerts
|

Bispyridinium (oxime) compounds antagonize the “ganglion blocking” effect of pyridostigmine in isolated superior cervical ganglia of the rat

Abstract: The "antidotal effectiveness" of several bispyridinium compounds (HGG 12, HGG 65, HGG 70, HI 6, HLö and HLö 12) against the acetylcholinesterase (AChE) inhibitor pyridostigmine was evaluated in isolated superior cervical ganglia of the rat. Compound action potential amplitudes were inhibited by pyridostigmine in a concentration-dependent manner. HI 6 and atropine proved to be the most effective compounds in antagonizing the "ganglion blocking" action of pyridostigmine. Their relative effectiveness (PE value) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The experiments were performed on TE671 cell line, which is medulloblastoma cell line endogenously expressing human embryonic muscle-like acetylcholine receptor (Schoepfer et al 1988). Even though the cell line is of neuronal origin, rhabdomyosarcoma properties has been described too (Stratton et al 1989).…”
Section: In Vitro Measurement Of Direct Nicotinic Receptor Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were performed on TE671 cell line, which is medulloblastoma cell line endogenously expressing human embryonic muscle-like acetylcholine receptor (Schoepfer et al 1988). Even though the cell line is of neuronal origin, rhabdomyosarcoma properties has been described too (Stratton et al 1989).…”
Section: In Vitro Measurement Of Direct Nicotinic Receptor Inhibitionmentioning
confidence: 99%
“…Antinicotinic action, which atropine lacks and which can prevent respiratory failure, has also been reported. Both neuromuscular blocking (Schlagmann et al 1990, Tattersall 1993, Chiou and Chang 1994 and ganglioblocking Tremblay 1979, Schlagmann et al 1990) types of antinicotinic action have been reported. However, the reported in vitro properties do not correlate with the antidotal observations in vivo.…”
Section: Introductionmentioning
confidence: 98%